2009
DOI: 10.1177/1753193408097489
|View full text |Cite
|
Sign up to set email alerts
|

The Deep (Motor) Branch of the Ulnar Nerve: A Detailed Examination of its Course and the Clinical Significance of its Damage

Abstract: The deep (motor) branch of the ulnar nerve is not frequently seen during surgery, but is vulnerable to penetrating injury and may be injured during surgery. Its anatomy is poorly described and its three-dimensional configuration is poorly appreciated. In this study, dissections of ten cadaveric specimens have been performed to demonstrate the branching pattern of the nerve and its skeletal relations have been clarified by superimposing images on radiographs. The deep branch passes downwards (anatomical posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 2 publications
1
14
0
2
Order By: Relevance
“…19e21 In accordance with Xie et al, 22 we found a single motor branch to the opponens pollicis in all cases, although, in 2 dissections, that branch bifurcated before entering the muscle. We found the distribution of the TDDBUN to be similar to previous reports, 20,23 including that of Atkins et al, 24 with a single motor branch to the transverse head of the ADP; 1 or 2 branches to the oblique head, which also innervated the deep head of the FPB; and a final branch to the FDI muscle. The average number of myelinated fibers in the OPB represented 64% of that of the TDDBUN, which renders the OPB an acceptable donor for TDDBUN reconstruction.…”
Section: Discussionsupporting
confidence: 90%
“…19e21 In accordance with Xie et al, 22 we found a single motor branch to the opponens pollicis in all cases, although, in 2 dissections, that branch bifurcated before entering the muscle. We found the distribution of the TDDBUN to be similar to previous reports, 20,23 including that of Atkins et al, 24 with a single motor branch to the transverse head of the ADP; 1 or 2 branches to the oblique head, which also innervated the deep head of the FPB; and a final branch to the FDI muscle. The average number of myelinated fibers in the OPB represented 64% of that of the TDDBUN, which renders the OPB an acceptable donor for TDDBUN reconstruction.…”
Section: Discussionsupporting
confidence: 90%
“…Second, connecting different anatomical layers may also be difficult as the deep motor branch of the ulnar nerve and its divisions (Atkins, Logan, & McGrouther, ; Gil, Shin, Lee, Koh, & Song, ) are fixed under the interosseous fascia, whereas more superficial radial lumbrical nerves are more mobile; thus it is quite difficult to dissect the deep motor branch of the ulnar nerve in the radial part of the deep palm for a segment long enough to be mobilized and finally to create a classical end‐to‐side with the recipient nerve cut and coapted to the healthy donor nerve. As an alternative, a reverse end‐to‐side between a cut lumbrical nerve coapted on the deep motor branch of the ulnar nerve or an end‐to‐end procedure could be claimed (denervating radial lumbrical muscles).…”
Section: Discussionmentioning
confidence: 99%
“…Although the origins and the precise courses of the nerves outside the thenar and hypothenar muscles have been morphologically documented using gross anatomy and microdissection methods [1][4], the precise intramuscular nerve distribution patterns of the thenar and hypothenar muscles have not been clearly described. Gross anatomy and microdissection have been the most commonly used methods, however, it should be noted that there are limitations when tracing nerve fibers from extramuscular branches to intramuscular terminal branches due to damaged muscle fibers and normal anatomical relationship between muscle cells and nerve fibers [5][6].…”
Section: Introductionmentioning
confidence: 99%